Caste ratio adjustments in response to perceived and realised competition in parasites with division of labour. (29th June 2018) - Lagrue, Clément; MacLeod, Colin D.; Keller, Laurent; Poulin, Robert
Abstract: Colonial organisms with division of labour are assumed to achieve increased colony‐level efficiency in task performance through functional specialisation of individuals into distinct castes. In social insects, ratios of individuals in different castes can adjust adaptively in response to external threats. However, whether flexibility in caste ratio also occurs in other social organisms with division of labour remains unclear. Some parasitic trematodes, in which clonal colonies within the snail intermediate host comprise a reproductive caste and a soldier caste, offer good systems to test the general nature of adaptive caste ratio adjustments. Using the trematode Philophthalmus sp. as model, we test whether trematode colonies shift their composition towards more soldiers when exposed to a sustained risk of invasion by a competitor parasite species, and/or when experiencing sustained, active competition. We also quantify the colony‐level fitness impact of caste ratio adjustments, measured as the colony's output of larval infective stages. We conducted two long‐term laboratory experiments on within‐snail trematode colonies. First, snails harbouring Philophthalmus colonies were exposed to different levels of invasion risk by another trematode species, Maritrema novaezealandense . Second, the structure of Philophthalmus colonies was quantified after a year‐long period of within‐snail competition with the other trematode species. When facing the risk of invasion by a competitor, independently of the level of risk, Philophthalmus colonies showed a significant shift towards producing more soldiers, resulting in altered caste ratio. Similarly, when experiencing actual competition by another trematode established in the same snail, Philophthalmus colonies also adjusted by producing significantly more soldiers. Greater investments in defense via more soldiers had negative impacts on the establishment and size of the competitor's colonies. Nevertheless, the presence of the competitor reduced the fitness (output of infective stages) of Philophthalmus colonies, although the production of more soldiers mitigated that effect. Our findings demonstrate that trematode colonies with division of labour are capable of adaptive caste ratio adjustments in response to both the perceived threat of competition and actual competition, with trade‐offs against reproductive success only apparent when soldier numbers are very high. Combined with results on social insects, our study suggests parallel adaptations of colonial organisms in phylogenetically disparate organisms. Abstract : The authors provide novel evidence for plasticity in colony structure in response to environmental threats in social organisms with division of labour, suggesting parallel adaptations in phylogenetically disparate organisms. Their findings demonstrate that trematode colonies with division of labour are capable of caste ratio adjustments in response to competition.